Legal Responsibility Of Cooperative Management And Supervisors For PKPU Bankruptcy Decision Number 37/Pdt. Sus-PKPU/2021/PN Niaga Sby - Chamdani Chamdani; Nobella Indradjaja; Budi Endarto; Suwarno Abadi; Joko Ismono (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this research is to understand the legal consequences of the dissolution of cooperatives that are declared bankrupt. In addition, this article discusses much more, related to the responsibilities of cooperative management for the dissolution of cooperatives, declared bankrupt. The method used in this study is a normative legal research method with a conceptual and legal approach with primary and secondary legal sources. The results of this study indicate that cooperatives have filed for bankruptcy because of their financial condition and their property is generally confiscated and cooperatives can be declared bankrupt and terminated by a decision by the government and a commercial judge. The legal consequences drawn by the Management of cooperatives for the liquidation of cooperatives that are declared bankrupt include: Bankruptcy is carried out at a meeting of cooperative members and lawsuits, Permission to complete the dissolution in other matters remains valid Dissolution of cooperatives by government decision, and there is no authority from the management to carry out dissolution . The management of the cooperative, in this case, is responsible individually or jointly for the losses of the cooperative where the cooperative management clearly fulfills the obligations of the cooperative management who acts intentionally or negligently